Evaluation of physical and psychological dependence in Mexican adult smokers, Encodat 2016 - Wayra Citlali Paz-Ballesteros; Luis Zavala-Arciniega; Daniela Sarahí Gutiérrez-Torres; Guadalupe Ponciano-Rodríguez; Luz Myriam Reynales-Shigematsu (Instituto Nacional de Salud Pública, 2019)
Objective. To evaluate the physical and psychological dependence of Mexican smokers and its association with physical, psychological and social factors. Materials and methods. The 2016 National Alcohol and Tobacco Drug Consumption Survey (n=7 331) was analyzed using the Fagerström nicotine physical dependence scale (FTND) and the short scale of psychological dependence on tobacco (TAPDSc). Bivariate analyzes and generalized ordinal logistic regressions were performed to evaluate the associated factors. Results. 82.3% of daily smokers and 98.8% of occasional smokers reported mild physical dependence, while 47.9 and 37.9% respectively reported moderate psychological dependence. The age of initiation of tobacco use, drug use, high alcohol consumption, and high emotional distress was associated with high levels of psychological dependence in all smokers. Conclusion. The exclusive use of FTND does not allow to adequately evaluate Mexican smokers. The physical and psychological dependence on tobacco should be assessed with independent and validated scales in this population.